COMPARATIVE STUDY ON THE EVALUATION OF THE GROWTH RATE COEFFICIENT FOR IBUPROFEN IN ETHANOL BY IN-SITU PAT AND CONVENTIONAL TECHNIQUES. (2015) - Rashid, Abdur; White, Ted; Howes, Tony; Litster, Jim; Marziano, Ivan
No abstract available